2020
DOI: 10.15252/embj.2020106230
|View full text |Cite
|
Sign up to set email alerts
|

SARS ‐CoV‐2 targets neurons of 3D human brain organoids

Abstract: COVID-19 pandemic caused by SARS-CoV-2 infection is a public health emergency. COVID-19 typically exhibits respiratory illness. Unexpectedly, emerging clinical reports indicate that neurological symptoms continue to rise, suggesting detrimental effects of SARS-CoV-2 on the central nervous system (CNS). Here, we show that a Düsseldorf isolate of SARS-CoV-2 enters 3D human brain organoids within 2 days of exposure. We identified that SARS-CoV-2 preferably targets neurons of brain organoids. Imaging neurons of or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
472
4
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 459 publications
(551 citation statements)
references
References 57 publications
(101 reference statements)
27
472
4
7
Order By: Relevance
“…For instance, viral antigen has been detected in the intestine of ferrets [29], hamsters [32,33], and rhesus macaques [42]. While viral RNA has been detected in human clinical brain samples [64], infection of cells of the central nervous system could thus far only be demonstrated experimentally in 3D human brain organoids [65]. Except for genetically modified mice expressing human angiotensin-converting enzyme 2 (ACE2) [39], the presence of SARS-CoV-2 antigen in animal or human brain samples has yet to be shown.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, viral antigen has been detected in the intestine of ferrets [29], hamsters [32,33], and rhesus macaques [42]. While viral RNA has been detected in human clinical brain samples [64], infection of cells of the central nervous system could thus far only be demonstrated experimentally in 3D human brain organoids [65]. Except for genetically modified mice expressing human angiotensin-converting enzyme 2 (ACE2) [39], the presence of SARS-CoV-2 antigen in animal or human brain samples has yet to be shown.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively mature neurons in day 60 COs exhibited substantial SARS-CoV-2 infection in cortical neurons within two days of exposure compared to Day 15 COs [67]. Similar viral load between two-and four-day post infection in COs indicated that the virus did not actively replicate in the COs [67]. Interestingly, the infected COs also showed an increase in early neurodegeneration-like phenotype as pTau (T231) was missorted from the axon to the soma and was colocalized with SARS-CoV-2 [67].…”
Section: Other Pathologiesmentioning
confidence: 93%
“…Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) causes severe upper respiratory tract infection and has also been shown to cause neurological symptoms [66]. Two recent studies have explored the neurological effects of this virus in COs [67,68] ( [68] published as preprint in bioRxiv). Day 15 and Day 60 COs were exposed to SARS-CoV-2 [67].…”
Section: Other Pathologiesmentioning
confidence: 99%
See 2 more Smart Citations